Crowd management in public transport to ensure social distancing for prevention of spread of COVID-19. (3rd February 2023) - Nigel, K. Gerard Joe; Jenisha, J.; Rajeswari, R.; Pamela, D.; Manimegalai, P.
There was global shock from COVID-19 epidemic. Social isolation is becoming more crucial as this delicate condition spreads swiftly. Public transit must be enhanced to stop the spread. This paper proposes an IoT method using LoRa technology that might reduce overcrowding and disease transmission in public buses. In the proposed, buses shall have LoRa transmitters and receivers. It is shown on the bus stop's LCD screen and announced over a speaker if the bus is within range of the receiver. An automatic door mechanism limits the number of people inside the vehicle. In the mobile app, the bus occupancy data is sent to Google Firebase. The app also indicates nearby buses, their occupancy, and their estimated arrival time. In certain cases, authorities may utilise this data to analyse and act. This simple technique would improve bus safety and contain COVID-19.